2014
DOI: 10.1002/ange.201310385
|View full text |Cite
|
Sign up to set email alerts
|

Fluorogel Elastomers with Tunable Transparency, Elasticity, Shape‐Memory, and Antifouling Properties

Abstract: Omniphobic fluorogel elastomers were prepared by photocuring perfluorinated acrylates and a perfluoropolyether crosslinker. By tuning either the chemical composition or the temperature that control the crystallinity of the resulting polymer chains, a broad range of optical and mechanical properties of the fluorogel can be achieved. After infusing with fluorinated lubricants, the fluorogels showed excellent resistance to wetting by various liquids and anti‐biofouling behavior, while maintaining cytocompatiblity. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…268 The resulting original omniphobic fluorogel elastomers displayed a broad range of optical and mechanical properties by tuning the chemical composition or the temperature that controlled the crystallinity of the resulting polymeric chains. These fluorogels also exhibited excellent resistance to wetting by various liquids, some antibiofouling properties, a shape-memory behavior, and maintained cytocompatibility.…”
Section: Fluorogelsmentioning
confidence: 99%
“…268 The resulting original omniphobic fluorogel elastomers displayed a broad range of optical and mechanical properties by tuning the chemical composition or the temperature that controlled the crystallinity of the resulting polymeric chains. These fluorogels also exhibited excellent resistance to wetting by various liquids, some antibiofouling properties, a shape-memory behavior, and maintained cytocompatibility.…”
Section: Fluorogelsmentioning
confidence: 99%
“…2 This provides inspiration for a new class of antibiofouling materials with a surface liquid layer, which is immobilized on a rough solid due to capillary forces and chemical affinity and which creates a low-adhesion interface. Such bio-inspired slippery liquid-infused porous surfaces (SLIPS) 43 have shown promising anti-bacterial performance in a polytetrafluoroethylene (PTFE)-based system, 44 and more recently in fluorogels 45 and vascularized polymer networks 46 . It would be beneficial to design slippery surfaces with a stable and continuously replenishable lubricant layer, particularly for medical tubing and catheter-relevant materials such as polyurethane and silicone and other flow-exposed medical materials, on which bacteria are known to attach and form biofilms within hours.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that many low surface energy materials, such as fluorinated polymers and siloxane, can weaken or minimize the interaction strength of polar or hydrogen bonding between foulants and membrane surfaces so as to promote the release of the attached foulants by hydraulic shear forces. 28,29 Previous publications demonstrated that Poly(ether sulfone) (PES) membranes modified by fluorine-containing modifiers exhibited low surface energies, high chemical resistance, and good mechanical strength. 30,31 In comparison to the unmodified PES membranes, surfacemodified PES membranes were susceptible to less fouling in the treatment of cutting machine oil/water emulsion by ultrafiltration, and could be effectively used to remove chloroform from water by pervaporation.…”
Section: Introductionmentioning
confidence: 99%